SymRK Regulates G-Protein Signaling During Nodulation in Soybean (Glycine max) by Modifying RGS Phosphorylation and Activity - Swarup Roy Choudhury; Sona Pandey (Molecular Plant-Microbe Interactions)
Molecular interspecies dialogue between leguminous plants and nitrogen-fixing rhizobia results in the development of symbiotic root nodules. This is initiated by several nodulation-related receptors present on the surface of root hair epidermal cells. We have shown previously that specific subunits of heterotrimeric G-proteins and their associated regulator of G-protein signaling (RGS) proteins act as molecular links between the receptors and downstream components during nodule formation in soybeans. Nod factor receptor 1 (NFR1) interacts with and phosphorylates RGS proteins to regulate the G-protein cycle. Symbiosis receptor-like kinases (SymRK) phosphorylate Gα to make it inactive and unavailable for Gβγ. We now show that like NFR1, SymRK also interacts with the RGS proteins to phosphorylate them. Phosphorylated RGS has higher activity for accelerating guanosine triphosphate (GTP) hydrolysis by Gα, which favors conversion of active Gα to its inactive form. Phosphorylation of RGS proteins is physiologically relevant, as overexpression of a phospho-mimic version of the RGS protein enhances nodule formation in soybean. These results reveal an intricate fine-tuning of the G-protein signaling during nodulation, where a negative regulator (Gα) is effectively deactivated by RGS due to the concerted efforts of several receptor proteins to ensure adequate nodulation. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.